The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.17239/l1esll-2021.21.01.10
|View full text |Cite
|
Sign up to set email alerts
|

An analytic description of ProjectExpert: An instructional reading program for ninth grade vocational students

Abstract: A significant number of ninth-grade students still struggles with proficiently comprehending texts. Moreover, their increasingly lowering motivation to read is alarming. Various educational interventions designed to enhance reading comprehension and/or motivation are available in the scientific field. However, a detailed description of its underlying principles is frequently lacking. This detailed description could provide genuine opportunities for replication, theory building, and dissemination into practice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…A ten-session intervention was developed based on the theoretical and empirical insights discussed in the introduction (e.g., Okkinga et al, 2018;Van Ammel et al, 2021).…”
Section: Core Components Of the Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…A ten-session intervention was developed based on the theoretical and empirical insights discussed in the introduction (e.g., Okkinga et al, 2018;Van Ammel et al, 2021).…”
Section: Core Components Of the Interventionmentioning
confidence: 99%
“…Our intervention was called "Iedereen Leesatleet" (Everybody Reading Athlete). Following Van Ammel et al (2021), the athlete metaphor referred to the high level of training and engagement required to comprehend texts (Duke et al, 2011;Goldman et al, 2016). The intervention condition students received no other reading comprehension instruction beyond the intervention itself.…”
Section: Core Components Of the Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of structured reading strategies helps to carry out deeper analyses of what is read, but little is known about the frequency of teaching this type of strategies in the classroom (Brevik, 2019), eventually, teachers play an important role in literacy worldwide, but often inexperience in the application of strategies to improve reading comprehension predominates (Tiba, 2023), Certainly, for educators who actively participate in literacy programs, the use of strategies that improve students' reading comprehension is of vital importance (Hungwe, 2019). At present there are many students who have difficulties in comprehension of texts and it is alarming that they have less and less motivation to read (Van Ammel et al, 2021), so it is recommended that teachers include specific instruction on reading strategies within their classes to counteract one of the most worrying problems of today's society such as the low reading ability of students (Kissau & Hiller, 2013), since for many students it is a skill which they struggle to perfect . Although it is always recommended to use reading strategies, sometimes it is necessary to first address the underlying problems of the student's language (Nippold, 2017), since several studies have shown that difficulties in reading comprehension can be associated with what is known as limited vocabulary or lexical poverty (Miranda et al, 2011), without neglecting that one of the main causes of the low level of reading comprehension of students is the ineffectiveness of the strategies employed by educators (Olifant et al,23).…”
Section: Introductionmentioning
confidence: 99%